Wall-building policy: nationalist space management and borderphobia as right-wing populists' tools for doing authoritarian politics - Żuk, Piotr; Żuk, Paweł (Frontiers in Political Science, 2024)
The article analyses the situation that arose after the crisis on the Poland-Belarus border in the second half of 2021. The authors use the term “borderphobia” to describe social, political and propaganda mechanisms that became a form of border space management used to legitimize and gain support for the actions taken by the right-wing populist government in Poland. The phenomenon of borderphobia can be a symbol of the symbiosis between political authoritarianism, nationalism and economic neoliberalism: the combination of these three forces affects the development of the “border industry” in Europe and in the world. The policy based on borderphobia facilitates the suspension of civil rights in the border area: this is what happened in Poland, where a state of emergency was introduced in the border area under the pretext of “border protection.” The case of building the wall on the Polish-Belarusian border can also show how the nationalist right in Poland can use the borderphobic discourse for political mobilization and in an election campaign to maintain their influence and political power in the country. The article indicates that although the leaders of right-wing populist parties believe that the slogans of defending the “security border” and building border walls can bring them political benefits, the example of the Law and Justice (PiS) party in Poland has shown that this is not always the case.